Reflection of youth slang in the language of the glossy magazines (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article gives a broad outline of youth slang and its most essential features including creativity, language economy, diversity, language play, semantic ambiguity reflected in the language of the glossy magazines and realized via a variety of language play, in particular, phonetic, graphic, word forming, lexical and metatextual.
Keywords: glossy magazines; youth slang; language play